New dinosaur, crocodylomorph and swim tracks from the Late Jurassic of the Lusitanian Basin: implications for ichnodiversity. (4th November 2020) - Castanera, Diego; Malafaia, Elisabete; Silva, Bruno C.; Santos, Vanda F.; Belvedere, Matteo
Abstract : New dinosaur (theropod and sauropod), crocodylomorph and swim tracks from Upper Jurassic units of the Lusitanian Basin, housed at the Sociedade de História Natural in Torres Vedras, are here described. They were collected from three different geological formations, the Praia da Amoreira‐Porto Novo (upper Kimmeridgian) and the Alcobaça (Kimmeridgian‐lower Tithonian) formations in the Consolação Sub‐basin and the Freixial Fm. (middle‐upper Tithonian) in the Turcifal Sub‐basin. Four different theropod morphotypes are identified as follows: cf. Jurabrontes isp., Megalosauripus cf. transjuranicus, Grallatoridae indet. and an indeterminate morphotype (Theropoda indet.) that have affinities with other Therangospodus ‐like tracks described in Europe. An indeterminate sauropod track is also identified. These five morphotypes suggest high saurischian dinosaur ichnodiversity, similar to that seen in other European Late Jurassic areas (e.g. the Swiss Jura Mountains), but represent just a portion of the higher diversity exhibited by the osteological record in the Lusitanian Basin. Further, one crocodylomorph pes track identified as Crocodylopodus isp. and swim tracks assigned to Characichnos isp., possibly also produced by crocodylomorphs, are also identified. The newly identified ichnotaxa, together with the older and other recent identifications, indicate ichnodiversity comparable with the richest coeval Upper Jurassic units.